Forecasting MAXIS stock price using Box-Jenkins Methodology / Hannani Irdina Hassan Nordin ... [et al.] - Hassan Nordin, Hannani Irdina; Hishamudin, Nur Hayanie; Abdul Wahab, Anis Humaira; Ab Malek, Isnewati (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The Malaysian economy is significantly shaped by the telecommunications sector. One of the first providers of mobile communications in Malaysia, Maxis was founded in 1995. The business, which was among the first to offer 4G services in 2013, is constantly updating its business strategy. Maxis is the market leader in this space as its 4G service is available to 15% of Malaysia's population. Maxis Berhad is a Malaysian investment holding company that owns the Maxis Group, which is a telecommunications company (Ullah, 2021.). The company's primary business activities include mobile prepaid and post-paid services, fixed line services, network facilities, other convergent telecommunications, digital and related services, such as fixed wireless internet broadband services (Taghizadeh et al., 2014). In the second quarter of 2021, Maxis Berhad generated a net profit of RM360 million as compared to RM342 million the year before. Due to increasing contributions from the postpaid and fibre sectors, the telecommunications business reported in a filing to Bursa Malaysia that revenue grew 5.3 percent to RM2.26 billion from RM2.15 billion earlier (Maxis, n.d). Maxis may accomplish this by employing forecasts to support the market's continued stability and profitability. Forecasts are crucial for all firms as they allow for the creation of data-driven strategies and the ability to make wise business decisions (Constangioara et al., 2009). The stock market and the economy usually operate in sync. Therefore, a strong stock market usually indicates that the economy is expanding. Predicting stock prices is important for achieving a rising stock market, as companies affect not only the stock market but also their position in the industry (Gayathri & Kalaivani, 2014). As a result, a precise stock price projection is necessary to entice additional investors to invest in the company. Consequently, it is crucial to complete this investigation in order to identify the best model for predicting Maxis stock prices. The investing.com website was used to retrieve the monthly opening stock price from May 2019 to October 2021. The data is used to assess and predict the opening stock values from November 2021 to October 2022.